Perbandingan Elevasi Digital Terrain Model Foto Udara dengan Pengukuran Terestris pada Kawasan Sumur Eksplorasi Migas - Muhammad Al’ Aziz Fariq; Dwi Arini; Defwaldi Defwaldi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Accurate elevation determination is one of the crucial aspects in oil and gas exploration activities, especially in the planning and management of well areas. This study aims to identify and compare the elevation of the Digital Terrain Model (DTM) obtained from aerial photography with terrestrial measurements, and to convert Digital Surface Model (DSM) data into DTM. The urgency of this study is driven by the need for accurate, efficient, and economical mapping methods, as well as validation of the methods used in topographic mapping. Digital Terrain Model (DTM) is a virtual model that adds elements such as fault lines and observations to correct artifacts from the original data, while DSM includes the height of all objects on the ground surface. The results showed that the largest elevation value in the aerial photo DTM was 14.416 meters at point L06 and the smallest elevation value was 6.567 meters at point A46, with an average elevation of 13.716 meters. Meanwhile, the comparison results of DTM elevation of aerial photography with terrestrial measurements showed the largest difference of 5.513 meters at point A46 and the smallest difference of -2.682 meters at point L21, with an average difference of 0.072 meters. The level of vertical accuracy (Z) based on the LE90 value is 0.2076 meters, which meets the geometric accuracy standard of 1:1000 class 1 scale according to BIG Regulation Number 15 of 2014. The results of this comparison are also supported by a 3D model of DTM elevation of aerial photography. This study provides an important contribution to the validation and improvement of the efficiency of topographic mapping methods based on aerial photography, as well as providing an overview of the accuracy of the data produced.